(untitled) (Journal of Atomic and Molecular Sciences, 2014)
The dynamical behavior of two-color ultrashort laser pulse propagating in a molecular medium 4,4'-bis(di-n-butylamino)stilbene (BDBAS) has been studied by employing an iterative predictor-corrector finite-difference time domain (FDTD) technique to solve the Maxwell-Bloch equations. The results indicate that the spectrum of electric field shows oscillation feature around the two-photon resonant frequency when the delay time exists due to the interaction between two sub-pulses. The optical limiting window turns narrower and the saturation value of output intensity gets larger with the presence of delay time compared with no delay time case. The dynamical TPA cross section is smaller with the increase of delay time. The studies suggest a method to modulate the nonlinear optical properties of the medium by controlling the delay time of the two-color pulse.